Enhancing hydrogen oxidation by Modulating Ru species on Ni3N@Mo2C through a Support-Induced Strategy - Akeno Nyaaba, Albert; Peng, Yao; Kang, Ziliang; Naz, Hina; Premlatha, Subramanian; Ji, Zhenyuan; Leetroy George, Stennard; Zhu, Guoxing (Chemical physics letters, 2024)
[Display omitted] •Ru/Ni3N@Mo2C composite was synthesized by; pyrolysis, hydrothermal, and wet-chemical route.•Synergistic effect between Ru and the support (Ni3N@Mo2C) optimized HOR kinetics.•Interfacial electronic interactions in Ru/Ni3N@Mo2C modulate Ru’s electronic structure.•The catalyst achieves a kinetic current density of 4.76 mA cmdisk−2 @50 mV. The use of hydrogen as an intermediator to convert and store electrochemical energy has been a subject of significant interest and focus. Unfortunately, the slow alkaline hydrogen oxidation reaction (HOR) is a barrier to further development of hydrogen–oxygen fuel cells. Ruthenium (Ru) has recently been investigated as a possible replacement for platinum (Pt) catalyst in the HOR because of the similar hydrogen binding energy (HBE) to Pt. Herein, Ru species was loaded on Ni3N@Mo2C support, which was used as an electrocatalyst for HOR. The catalyst presents an exchange current density and kinetic current densities of 3.05 and 4.76 mA cmdisk−2 that are 2 and 1.4 times greater than that of commercial Pt/C, respectively. The findings indicate that the Ni3N@Mo2C support reduces the hydrogen binding energy on Ru sites. This improves the Volmer step for HOR and increases the catalytic activity. This study thus provides some guidance in the designing of HOR catalysts for efficient hydrogen energy conversion.